Crystal structure of diclazuril, C17H9Cl3N4O2. Issue 4 (December 2022) - Kaduk, James A.; Gates-Rector, Stacy; Blanton, Thomas N.
Abstract : The crystal structure of diclazuril has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional theory techniques. Diclazuril crystallizes in space group P2 1 /a (#14) with a = 27.02080(18), b = 11.42308(8), c = 5.36978(5) Å, β = 91.7912(7)°, V = 1656.629(15) Å 3, and Z = 4. The crystal structure consists of layers of molecules parallel to the ac -plane. A strong N–H⋯O hydrogen bond links the molecules into dimers along the a -axis with a graph set R2, 2(8) . The powder pattern has been submitted to ICDD for inclusion in the Powder Diffraction File™ (PDF®).